2002
DOI: 10.1007/s005950200092
|View full text |Cite
|
Sign up to set email alerts
|

A Gastric Duplication Cyst with an Aberrant Pancreatic Ductal System: Report of a Case

Abstract: We report an extremely rare case of a gastric duplication cyst together with an aberrant pancreatic ductal system, which communicated with the stomach rather than the pancreatic ductal system with no evidence of pancreatitis. A 46-year-old woman developed severe abdominal pain after a 10-year history of occasional mild abdominal pain. Upper gastrointestinal barium radiography showed a rigidity of the stomach wall, and gastroscopy revealed a fistula orifice at a greater curvature of the gastric body. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 6 publications
1
22
0
1
Order By: Relevance
“…A gastric duplication cyst communicating with an aberrant pancreatic duct is rarer. Fifteen cases (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have been reported, and several cases with recurrent acute pancreatitis have also been reported (Table 1). It has been suggested that the underlying cause involves obstruction of the pancreatic duct by viscous mucus secretions, ulcer bleeding or biliary sludge.…”
Section: Introductionmentioning
confidence: 99%
“…A gastric duplication cyst communicating with an aberrant pancreatic duct is rarer. Fifteen cases (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) have been reported, and several cases with recurrent acute pancreatitis have also been reported (Table 1). It has been suggested that the underlying cause involves obstruction of the pancreatic duct by viscous mucus secretions, ulcer bleeding or biliary sludge.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with gastric duplication cysts communicating with aberrant pancreatic duct, abdominal pain is often related to acute pancreatitis. Recurrent acute pancreatitis caused by this anomaly have been reported in 12 cases (66%) (4)(5)(6)(7)(8)(9)(11)(12)(13)(14)16,17). Oeda et al (17) reported that there were not significant differences between the patients with pancreatitis and without pancreatitis in terms of either sex or age.…”
Section: Discussionmentioning
confidence: 95%
“…In the patients with this anomaly, a definitive diagnosis was rarely made preoperatively and several operative explorations were required in some cases (11,12). The aberrant pancreatic ductal system was revealed by endoscopic retrograde cholangiopancreaticography (ERCP) in majority of the cases diagnosed preoperatively and the usefulness of ERCP was emphasized (6,13). To our knowledge, there are only a few reports of spiral computed tomography (CT) (13) and no previous report of multidetector CT and magnetic resonance imaging (MRI) findings of this unusual anomaly.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations